Collaborative commerce in supply chain management: A study of adoption status in Malaysian Electrical and Electronic industry - Chong, Alain Yee Loong; Ooi, Keng Boon (Asian Network for Scientific Information, 2008)
The principle objective of this study is to examine the adoption status of Collaborative Commerce (C-Commerce) in the Malaysian Electrical and Electronic (E and E) organizations. Original research using a self-administered questionnaire that was distributed to 400 Malaysian E and E organizations. Data were analyzed by employing descriptive statistics. In general, the adoption level of C-Commerce tools in the Malaysian E and E industry is still considered low with an average mean of 3.011. Based on the tools adopted, most organizations are utilizing C-Commerce for their supply chain execution. Among tools with lower adoption, they are mainly supply chain planning tools such as capacity planning tool and business strategy tool. This research enables organizations to have a better understanding of the current status of C-Commerce adoption level for SCM in the Malaysian E and E industry. This research have addressed previous lack of study in the adoption status of C-Commerce in the Malaysian E and E industry.